No Place like (the) Home - Michael Hughes (Oz, 1997)
Asked to design a retirement home on a heavily wooded site in northeast Georgia, this project has developed as a critique of contemporary cultural and spatial responses to aging. The program—a single family residence constructed of low-maintenance materials with all major functions located on the ground floor for potential handicap accessibility—prompted my initial fear of, and subsequent fascination with, retirement in terms of repression and mortality.